Analyzing Cyclops Application Acceptance in Telkomsel Pamasuka using IDT and TAM - Kadir, Muhammad Idham; Tricahyono, Dodie (Penerbit Goodwood, 2023)
Purpose: In this thesis, we will examine how much employee acceptance in the Pa Masuka Area, especially “Network” and “Sales', which totals around 522 people to the CYCLOPS application using the Innovation Diffusion Theory (IDT) and Technology Acceptance Model (TAM) methods, then an online survey is conducted. Research Methodology: Data analysis was performed using a Structural Equation Modeling (SEM) model. Results: Digitization of processes at Telkomsel continues to be carried out to increase the effectiveness of employee work, including in the Pausuka Area, especially in the Area Network Operations Sub-Directorate of Pausuka which is responsible for 18,000 sites serving 30 million customers based on April 2023 data.CYCLOPS is a supporting application for digitizing processes that makes it easier for employees, especially the